Products of the Same Master Copy: Deification of Body Limbs in Book of the Dead Spell 42 in TT 11 and pHanover KM 1970.37 - Llanos, Lucía Díaz-Iglesias (Zeitschrift für ägyptische Sprache und Altertumskunde, 2018)
The so-called Gliedervergottung section of BD 42 displays close textual and iconographic features in two Eighteenth Dynasty sources: the burial chamber of the tomb of Djehuty (TT 11) and the papyrus of Baksu (Hanover KM 1970.37). Both sources will be presented, transcribed, and compared to highlight their derivation from the same master copy. Finally, some thoughts on what dublettes can tell us about Book of the Dead Vorlagen and scribal activities will be offered.